2015
DOI: 10.1111/jdv.13222
|View full text |Cite|
|
Sign up to set email alerts
|

Use of biologics for psoriasis in Central and Eastern European countries

Abstract: There exists a disconnect between the European psoriasis treatment guidelines and the various CEE country-specific biologic coverage eligibilities. The cost of biologic therapy for psoriasis is not solely and directly responsible for the different use rates amongst the CEE countries. Psoriasis may not be perceived by all payers as a serious disease that can be successfully treated in a cost-effective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 29 publications
2
47
1
3
Order By: Relevance
“…Product information for the use of all biologics for psoriasis [3][4][5]13] in the present study. PUVA, psoralen and ultraviolet A light.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Product information for the use of all biologics for psoriasis [3][4][5]13] in the present study. PUVA, psoralen and ultraviolet A light.…”
Section: Resultsmentioning
confidence: 99%
“…Or who have a contraindication to Absolute contraindications were always considered as exclusion criteria [4][5][6][7][8][9][10][11][12][13][14]. Contraception was suggested for men and women with methotrexate and only for women with acitretin and biologics, and its refusal was considered an exclusion criterion for those therapies [10] Relative contraindications were carefully evaluated individually, and treatment was not begun if they were not removed or controlled with adequate interventions [10] Drug interactions were carefully evaluated in each individual case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incentive policies applied to biosimilars are heterogeneous across countries. At the time of the review, pharmaceutical prescription budgets or prescription quotas were reported in place for half of the countries [14,19,[39][40][41][42][43] Financial incentives or penalties measures were found in countries applying pharmaceutical prescription budgets and/or prescription quotas, but were reported as not frequently enforced (Belgium, Germany) or enforcement was not documented in the literature (Greece, Italy, Sweden, the UK) [14,39,41,42,44] Except for Poland, where switching by the physician is generally encouraged [45][46][47], some countries (Belgium, France, and Italy) do not recommend switching even if they do not prohibit it [14,39], while some other countries might recommend it in some specific cases (e.g., products with same producer (Germany, Sweden) [14], sufficient elapse time between two treatments, or in case of treatment failure (Hungary) [46,47]. In Spain, patients who started biologic therapy usually continue to receive the same medicine, and all decisions should be taken by physicians [13].…”
Section: Resultsmentioning
confidence: 99%
“…Hungarian guidelines permit switching between a suitable biosimilar and the original medicine in clinically justified cases (due to adverse events or a lack of efficacy), and at least 1 year after terminating the previous treatment [74,85]. In the UK, NICE left treatment choice to prescribers [30], but different -and often conflicting -recommendations are published by scientific associations; for instance, the British Society of Gastroenterology recommends switching those patients who are in a stable clinical response or remission on the reference medicine [86], while the National Rheumatoid Arthritis Society and the British Society for Rheumatology recommend that stable patients should not be switched [87].…”
Section: Demand-side Policies For Biosimilarsmentioning
confidence: 99%